Build It But They May Not Come: Subjective Factors In Participation Decisions Among Under-represented Groups - Ralf St. Clair (Adult Education Research Conference, 2006)
This discussion presents a model for thinking about participation in learning for under-represented groups. The model is designed specifically to be useful for thinking about this question in the context of policymaking rather than a re-theorization of participation itself.
Keywords: Adult education models; policy; under-represented groups